PENGARUH PERAN ORANG TUA DAN GURU TERHADAP KEDISIPLINAN BERIBADAH SISWA MA AL-MUKARROM KECAMATAN KAUMAN KABUPATEN PONOROGO - Imam, Imam Hadi Susilo; Salsabila Aufa Khairunnisa; Happy Susanto; Ayok Ariyanto; Kholis (TARBAWI:Journal on Islamic Education, 2024)
This research was carried out to examine the influence of the role of parents and teachers on the discipline of worship of MA AL-Mukarrom students. This type of research is descriptive quantitative. The data collection technique used in this research is a questionnaire. The research instrument is a questionnaire sheet. Hypothesis testing using multiple linear regression analysis and F test. The conclusion of this study is that there is a significant influence between the role of parents and teachers on the discipline of worship of MA AL-Mukarrom students in Kauman District, Ponorogo Regency. With the results of the regression model obtained in the form of Y = 45.442 + 0.091 (X1) + 0.318 (X2) + e, where Y is the worship discipline variable, X1 is the parent role variable, and X2 is the teacher role variable. The results of the F test also provide the conclusion that the role of parents and teachers simultaneously affects the discipline of worship of MA Al-Mukarrom students. Based on the determination test, it is concluded that the two independent variables affect 21.4% of the discipline of worship. This means that the role of parents and teachers is quite a big influence as an encouragement from external parties on the discipline of student worship. Worship in this study is limited to the context of obligatory prayers, reciting the Quran and giving alms.